2017
DOI: 10.22438/jeb/38/5(si)/gm-34
|View full text |Cite
|
Sign up to set email alerts
|

Integration of high seeding densities and criss cross row planting pattern suppresses weeds and increases grain yield of spring wheat

Abstract: Aim : Methodology :Results : Interpretation :Eco-friendly and sustainable weed management tactics are advocated by weed managers worldwide. In order to develop such a technology, an experiment was undertaken at Agronomic Research Area of the Faculty of Agriculture, Gomal University, Dera Ismail Khan, Khyber Pakhtunkhwa province, Pakistan during rabi season.A 2-factor experiment was laid out in a randomized complete block d e s i g n w i t h s p l i t p l o t arrangement with the planting patterns (line and cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…m −2 ). Similar conclusions are presented by Hussain et al [13], who compared the wheat response to seed rates of 50, 100, 150 and 200 kg ha −1 . The increase in yield shown in this study resulted from the decreased weed pressure along with an increase in the sowing density of wheat.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…m −2 ). Similar conclusions are presented by Hussain et al [13], who compared the wheat response to seed rates of 50, 100, 150 and 200 kg ha −1 . The increase in yield shown in this study resulted from the decreased weed pressure along with an increase in the sowing density of wheat.…”
Section: Introductionsupporting
confidence: 87%
“…Moreover, there was an increase in generative tillers per plant in Persian wheat and a reduction in number of vegetative tillers per plant in Indian dwarf wheat. In the study by Hussain et al [13] among the yield components, only the number of generative tillers per m −2 increased in proportion to the increase in the grain yield at higher seed rates. According to Wu et al [41], high sowing density as a purposeful agricultural practice increases yields, reduces weed infestation and increases sustainability by increasing biomass and soil cover during the growing season of the plants, which reduces nutrient loss and erosion.…”
Section: Morphological and Agronomic Traitsmentioning
confidence: 89%
See 1 more Smart Citation
“…Around 18.4-23.4% lower weed density and biomass were observed under criss-cross sowed wheat crop compared to a line-sown crop using 100 kg seed ha-1. 37 Chhokar et al (2017) 16 found a 2.4% higher yield with reduced weed infestation under criss-cross sowing than conventional line sowing. Criss-cross wheat sowing at 22.5 cm row spacing can manage the weeds equal to the 15 cm row spacing unidirectional sowing, but yield remained 5% greater in the criss-cross way of sowing.…”
Section: Row Orientationmentioning
confidence: 99%